Processing nanoparticle–nanocarbon composites as binder-free electrodes for lithium-based batteries - Marya Baloch (19720126) (2017)
The processing of battery materials into functional electrodes traditionally requires the preparation of slurries using binders, organic solvents, and additives, all of which present economic and environmental challenges. These are amplified in the production of nanostructured carbon electrodes which are often more difficult to disperse in slurries and require more energy-intensive and longer processing. In this study we demonstrate a new process for preparing binder-free nanocarbon/nanoparticle (Fe–C) composite electrodes and study the effect of processing on the nanocomposite’s cycling performance in lithium cells. The binder-free electrodes were prepared by a two-step method: pulsed-electrodeposition of iron-based catalyst followed by chemical vapor deposition of a carbon film. SEM and TEM of the Fe–C showed that the active materials have a fibrous and tortuous morphology with disordered nanocrystalline domains characteristic of an amorphous carbon. The Fe–C electrodes showed good mechanical stability and an excellent cycle performance with an average stable capacity of 221 mAhg−1, and 85% capacity retention for up to 50 cycles. By reducing the number of processing steps and eliminating the use of binders and other chemicals this new method offers a “greener” alternative than current processing methods. Other Information Published in: Materials for Renewable and Sustainable Energy License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s40243-017-0105-5